Segmenting Investors on their Biases Manifested in Investment Decision-Making by Individual Investors - Fatima, Afreen; Sharma, Jitendra Kumar (SEISENSE (PRIVATE) LIMITED, 2021)
Purpose- This study proposes to identify the certain biases affecting investor decision-making and to segment investors accordingly. Design/Methodology- A quantitative research method was applied to measure the existence and impact of the biases on investment decision-making. A survey was administered among the stock market investors in Uttar Pradesh. Factor analysis was used to extract those biases that significantly impact investment decision-making and their mean score to assess the level of agreement that affects their investment decisions. Findings - The finding reveals that eight extracted factors affect the investment decisions and accordingly segment them on the biases they exhibit. The investors tend to fall into Imitator, Stereotypical, Independent Individualist, Risk Intolerant, Efficient Planner, Confident, Passive, and Competent Confirmer. The Imitators, Independent Individualists, and Confident investors show their higher level of agreement that highly affects their equity investment decision-making. Practical Implication- This study provides a base to segment the investors on their biases. In addition, it will help in customizing the investment recommendation based on their biases to improve the investment decisions.